2015
DOI: 10.1017/jfm.2015.110
|View full text |Cite
|
Sign up to set email alerts
|

Surface water waves over a shallow canopy

Abstract: The dynamics of water waves passing over a vegetation canopy is modelled theoretically. To simplify the geometry, we examine a periodic array of vertical cylinders fixed on a slowly varying seabed. The macroscale behaviour of wave attenuation is predicted based on microscale dynamics between plants. Interstitial turbulence is modelled by Reynolds equations with a locally constant eddy viscosity determined by energy considerations. Using the asymptotic method of multiple-scale expansions, the slow evolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…The overall Morison inertia coefficient, C m , is set as 2.0, which is the potential flow-based value for cylinders in cross flow. It is worth noting that some early studies for periodic waves and current separately have demonstrated that C d can be larger for cylinder array than an isolated cylinder, see Cheng and Nguyen (2010); Wang et al (2015).…”
Section: Resultsmentioning
confidence: 99%
“…The overall Morison inertia coefficient, C m , is set as 2.0, which is the potential flow-based value for cylinders in cross flow. It is worth noting that some early studies for periodic waves and current separately have demonstrated that C d can be larger for cylinder array than an isolated cylinder, see Cheng and Nguyen (2010); Wang et al (2015).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, examining the 2D velocity profiles in detail in Section 4, we find that the flow velocities in the cases with relatively high depths (Cases 6 and 7) are There is also a limitation such that the current framework could only deal with the stable, quasi-steady and macroscopically unidirectional flow situation. We formulate SW equation (27) without inertial force effects like many previous studies. 45 However, the inertial force is dominant in dense forests under unsteady-state flow conditions especially at the tsunami runup.…”
Section: Discussionmentioning
confidence: 99%
“…In some previous studies with purposes similar to ours, the length of the LTD in the overall flow direction was reduced to accommodate only a few trees. For example, Wang et al 27 employed a periodic LTD, called a unit cell, in which cylinders are vertically located to develop a surface water model. Lee and Yang 31 also investigated flows in a 2D unit cell with emerged cylinders.…”
Section: Setup Of the Ltdmentioning
confidence: 99%
See 1 more Smart Citation
“…La capacité à atténuer les forçages hydrodynamiques est dépendante des caractéristiques biométriques comme la densité (PAUL & AMOS, 2011 ;KOFTIS et al, 2013), l'indice de surface foliaire (PAUL et al, 2012), la flexibilité (PERALTA et al, 2008 ;PUJOL & NEPF, 2012), le ratio de submersion (MANCA et al, 2012 ;JOHN et al, 2016), et des caractéristiques morphologiques (étendue -GAMBI et al, 1990, fragmentation -FONSECA & KOEHL, 2006 de chaque espèce (ELGINOZ et al, 2011). À notre connaissance, seules deux études récentes se sont intéressées au rôle de la végétation en très faible profondeur (WANG et al, 2015) dernières produisant les vents les plus intenses (figure 1b). Trois sites ateliers ont été choisis pour leurs différentes expositions aux forçages hydrodynamiques et leur variété de longueur de fetch (figure 1a).…”
Section: Introductionunclassified